The Relative Importance of Work as a Factor in Life Satisfaction - White, Terrence (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1981)
This study assesses the impacts of job satisfaction on life satisfaction through the analyses of data obtained from a sample of respondents who held full-time employment.